Postgraduate Paediatric Education in Indonesia - H.E. Monintja; W.T. Karjomanggolo; R. Sutejo (Paediatrica Indonesiana, 1979)
Previously the objectives of the postgraduate training program throughoutIndonesia were not clearly defined. The problems which served as objective determinants were also not defined. At present the Indonesian Paediatric Association, with her Board of Specialists, has succeded in laying down the fundamental of the curriculum of Indonesian Paediatrician. The government as well as the Indonesian Paediatric Association now realize that the postgraduate paediatric education system should be a "system approach" to solve health problems in IndonesiaThe objectives of the training of paediatricans in the Department of Child Health Medical School University of Indonesia has been described in another monograph.To achieve the objectives the learning experience is as follows :1. Assignment in the wards and field practice areas, 2. Case presentations3. Death Conference, 4. Problem case discussion 5. Chart (medical records) discussion, 6. Emergency duties, 7. Guest lectures, 8. Home lectures, 9. Journal readings, 10. Experience in education, 11. Experience in research.